Gold Nanoparticles Chain Waveguide with Enhanced Transmission Method and Spectral Coding - Cinar, C.; Sengor, T. (ELECTROMAGNETICS ACAD, 2012)
In this study a known waveguide consisting of fifteen gold cubic nanoparticles is examined using 3D FDTD method with Drude model and auxiliary differential method. The magnitude of transmission rate to the end point of the waveguide is managed to be increased by using total fourteen particles without changing the length of the chain by just removing the 4th particle, where all the other parameters are unchanged. By not deploying 4th particle there became two separate chain which enlightened by single gauss laser beam at the same time and this effect makes surface plasmon polarizations boosted twice like a cascade amplifier. In addition to one removal, two and three removal of particles at a time is studied and their spectral transmission rate characteristics are given as a communication coding or data storage information placement location.
Keywords: Engineering; Physics